Perceptions of physiotherapists regarding their role in the management of patients with mental health disorders - Lord, Sandy (My University, 2018)
Introduction: Physiotherapy in mental health is not well established in South Africa. Both at undergraduate and postgraduate training levels, the role of physiotherapy in the management of mental health disorders is not given much consideration. However, physiotherapists can play a key role in managing patients with mental health disorders. The role of physiotherapy in the management of patients with mental health disorders is still unclear in South Africa. Aim: To determine the perceived role of physiotherapists in the management of patients with mental health disorders. Methodology: Physiotherapists working in mental health facilities were invited to participate in this qualitative study. One-on one, semi-structured interviews were conducted in order to explore the participants' perceptions of their role in the management of patients with mental health disorders and to identify barriers and facilitators to their management. Inductive and deductive analysis was used to analyse the data. Results: Seven physiotherapists were interviewed, of which only one worked in a public facility. Analysis yielded two main themes - lack of consensus regarding the role of physiotherapy in mental health and barriers and facilitators to management Conclusion: Physiotherapists in this study were uncertain about their role in the management of patients with mental health disorders largely due to a lack of knowledge of the role of physiotherapy in mental health, both at an undergraduate and postgraduate level. Most physiotherapists had less than five years' experience working with patients with mental health disorders. The perceived barriers were largely due to an unconducive work environment and lack of knowledge and the perceived facilitators being a favourable work environment as well as the attributes of the physiotherapist.
A research report submitted in partial fulfilment of the requirements for the degree of Masters in Physiotherapy to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, 2018